The KONSEP KEADILAN PEREMPUAN DALAM ISLAM PERSPEKTIF ASGHAR ALI ENGINEER - Rauzatul Jannah; Umi Sumbulah (University of Islam Malang, 2024)
The injustice of women is still rampant today. People often use religious teachings to perpetuate patriarchal systems. The purpose of this study is to examine the concept of women's justice in Islam from the perspective of Asghar Ali Engineer. This research uses qualitative methods with a library research approach, namely research conducted by reading the concept of equality of women used in the book